Thermo-fluid characteristics and exergy analysis of a twisted tube helical coil - Mahmoud Abdelmagied (Scientific Reports)
Abstract In the present investigation, the exergy of an innovative technique involving the integration of curved helical tubes with twisted passages was experimentally presented. This technique aims to improve the thermofluid characteristics by involving the swirl intensity of fluid flow in a twisted tube helical coil (TTHC). Six identical geometries with different pitch ratios $$Υ$$ of 36 mm, 54 mm, and ∞ (smooth/no twisted) were experimentally explored at two different inner tube profiles of triangular and square cross-sections in counter flow arrangements. The experimental runs were carried out at 10,300 ≤ Re i ≤ 37,800 and 2400 ≤ Re o ≤17,600 for both the inner and annulus fluids, respectively. The results showed that the Nusselt number, Nu, increased by 39.6% and 41.5% for triangular and square inner twisted cross-section profiles, respectively, at a $$\it Υ$$ of 36 mm at the expense of increasing f by 37.6% and 60.7%, respectively. The results also showed that the thermal performance factor reached 1.3 and 1.25 for a $$\it Υ$$ of 36 mm for the triangular and square inner twisted tube profiles, respectively. A comprehensive study is performed to analyze the TTHC from thermal, frictional, and exergetic viewpoints. New correlations for expecting the annulus Nu o and f o are presented.